An analytical model for the loading capacity of splice-retrofitted slender timber columns. (15th December 2020) - Li, Hongmin; Qiu, Hongxing; Lu, Yong
Highlights: The analytical model for the loading capacity of splice timber columns is proposed. The buckling modes and stress distributions of splice columns are investigated. The theoretical model is validated by the test data and numerical results. The model can predict the axial compressive strength of a retrofitted column. The model can be applied for the historical retrofitted timber columns in practice. Abstract: Retrofitting timber columns in traditional timber structures with a steel jacketed splice joint has advantages of aesthetic appearance and similar mechanic performance to the intact columns as compared to conventional simple splice columns. The axial compression behavior of such retrofitted splice columns has been studied experimentally in detail. However, there is still a lack of a calculation model for their axial compressive strength and general guideline for their design. The objective of this study is to establish a theoretical calculation model for this type of retrofitted splice columns. Firstly, a theoretical model for the axial compressive strength of splice columns retrofitted with a steel jacket is proposed considering the contact stresses at a splice joint and the relevant stability theory. Secondly, the buckling modes of splice columns and the actual stress distributions at the splice joints (i.e. the compressive stresses at the steel-timber and timber-timber interfaces) are thoroughly investigated. Finally, the theoretical model is validated by the experimental data and finite element analysis results with different splice parameters. Comparisons show that the theoretical calculations in terms of the bearing capacity and stability coefficient agree well with the experimental results. The proposed theoretical model is also shown to be suitable for predicting the axial compressive strength of a retrofitted splice column with the location of the splice from the column end ranging from 1/5 to 1/2 of the column length. The relative errors in the theoretical bearing capacities with respect to the finite element results are found to be less than that using the stability coefficient. From the analysis results, the length of the splice and the total length of the steel jacket are recommended to be in the range of 0.5 1.5 and 2 4.5 times of the column diameter, respectively. This proposed theoretical model can be applied in the retrofitting design of timber columns in historical timber structures, and it can also be applied in the development of new large-space timber structures where splice columns may be incorporated.